A study of heat transfer generalization for a cooling system with mineral media coatings - Genbach, A.A.; Bondartsev, D.Yu. (Karagandy University of the name of academician E.A. Buketov, 2025)
Studies of heat transfer in cooling systems with natural material coatings have been carried out.The phenomenon of flame spin detonation was observed at an oxidizer excess ratio below unity, with the spraying process being intensified up to sixfold. The coatings demonstrated high reliability compared to other accelerated systems. The maximum specific heat fluxes on the coating range from 2 to 20×10⁶ W/m², with oscillation frequencies reaching 200 Hz. The overheating range of the coating was (20–75) K. The granulometric composition of the materials was obtained, and the hydrodynamic operating modes of the burners were selected. A model was developed for the interaction of a supersonic detonation gas jet of the thermal tool acting normally to the coating. The experimentally determined heat transfer coefficients were found to be 5–6 times higher than those predicted by laminar theory, and several times lower than those predicted by turbulent heat transfer laws. The particle flight time, powder diameter, as well as the ultimate compressive and tensile stresses of the coating were determined. The main practical application of the research is thermal protection through cooling with natural coatings (quartzites, granites, teschenites, marbles, tuffs) for highly forced and high-intensity structures in the fields of energy, metallurgy, and mechanical engineering. The primary industrial implementation of the research is the use of a thermal tool for spraying, processing of rocks, drilling, and cutting of reinforced concrete structures during modernization and reconstruction of enterprises.
Keywords: heat and mass transfer; coatings; thermal tools; combustion chamber; nozzles; detonation torch